Consumo alimentar em escolares: estudo baseado nos “10 passos da alimentação saudável para crianças” - Weber, Ana Paula (Universidade do Vale do Rio dos Sinos, 2012)
With the process of urbanization, industrialization and technological development, major changes have occurred in patterns of diet and physical activity of populations worldwide, which have been translated into overweight and obesity. In Brazil, about 34% of children aged 5 to 9 years are overweight and 14.3% are obese. Among the strategies to change this epidemiological profile are the dietary guidelines, as developed by the Ministry of Health to assist the Brazilian population to adopt a healthier lifestyle. However, few studies have evaluated the extent to which the population is following the recommendations of the Guide, especially in children. The objective of this study was to evaluate the performance of the ‘10 Steps of Healthy Eating for Children’ and its associated factors in first grade students from elementary public schools in São Leopoldo, RS, Brazil. It is a cross-sectional study, with 813 students. The data was obtained by applying a standardized questionnaire, pre-coded and pre-tested for mothers/guardians, by trained interviewers. The questions were related to actual diet and physical activity of the students, as well as the demographic and socioeconomic characteristics of them and their families. Bivariate analyzes were conducted between the independent variables and each "Step" by the Chi-Square test for heterogeneity or linear trend, considering a significance level of 5%. Step 2 (including cereals, tubers, etc. between meals) was the most followed by children (99.8%). The two "steps" less performed were frequently those involving restrictive measures, such as avoiding fatty foods/fried (Step 6) and avoid sweets (Step 7), respectively, 12.8% and 3.8%. In general, students whose mothers/carers and householders were younger and had less education followed more frequently some of the "Steps". Our study indicate a poor prognosis for this population and a need for further studies to elucidate the relationship between the exposure variables and the achievement of “Steps”.
Keywords: Guias alimentares; Consumo alimentar; Escolares; Food guide; Food consumption; Students; ACCNPQ::Ciências da Saúde::Saúde Coletiva